2015
DOI: 10.1515/jcim-2014-0060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of daily drinking of Aloe vera gel extract on plasma total antioxidant capacity and oral pathogenic bacteria in healthy volunteer: a short-term study

Abstract: Our data revealed that A. vera gel extract significantly increased plasma TAC, and decreased the number of Lactobacillus spp. without any clinical side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…In addition, the serum resistance on ex vivo oxidation in the presence of Cu did not differ in any group or between groups during the intervention period. In contrast, a recent study observed that daily consumption of higher amount of Aloe vera extract (250 mL) increased total antioxidant capacity of serum after 14 days [ 49 ]. Concerning other plant extracts, the consumption of green tea extract in capsules, reduced the LDL ability against oxidation in healthy men [ 59 ] while the consumption of tea did not affect urinary 8-isoprostane in a healthy population [ 60 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the serum resistance on ex vivo oxidation in the presence of Cu did not differ in any group or between groups during the intervention period. In contrast, a recent study observed that daily consumption of higher amount of Aloe vera extract (250 mL) increased total antioxidant capacity of serum after 14 days [ 49 ]. Concerning other plant extracts, the consumption of green tea extract in capsules, reduced the LDL ability against oxidation in healthy men [ 59 ] while the consumption of tea did not affect urinary 8-isoprostane in a healthy population [ 60 ].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, data also support that Aloe vera results in slower vitamins’ absorption and increases the bioavailability of co-administrated vitamins E and C in human subjects [ 33 ]. However, few human clinical trials were conducted in order to study the effects of the Aloe vera consumption [ 49 , 50 ] or supplements that combine vitamins and plant extracts [ 51 , 52 ], on oxidative stress markers. Concerning tea extract, it is reported to have a potential anti-oxidant effect in humans and specifically [ 53 , 54 ] green tea extract supplementation improves antioxidant status of male students after 4-weeks [ 55 ] and increases glutathione peroxidase and catalase activities in male non-smoking subjects after 6-month consumption [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The daily consumption of Aloevera gel extract was found to decrease the amount of oral pathogenic bacteria, Lactobacillus spp and Streptococcus mutans in saliva. In addition, the gel extract helps to increase plasma total antioxidant ability, with no clinical adverse effects (21).…”
Section: Discussionmentioning
confidence: 99%
“…The low plaque index found in the study participants may be explained by the fact that Aloe vera is a high antimicrobial agent. Aloe vera has shown antibacterial activity against a number of bacteria, mainly Streptococcus mutans, which are responsible for its antiplaque effect (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that Aloe vera gel extract significantly increased plasma total antioxidants in healthy volunteers. (17) There is insufficient scientific evidence on the efficacy of Indonesian Aloe vera extract prepared from local cultivars and on its mechanism of action. Additional work is required to probe into the antidiabetic, antimicrobial, and antioxidant properties of Indonesian Aloe vera extract.…”
Section: Introductionmentioning
confidence: 99%